Analisis Faktor-Faktor Yang Menyebabkan Masyarakat Memilih Pembiayaan Dengan Sistem Tanggung Renteng di PT. Permodalan Nasional Madani (Persero) (Studi Kasus Kota Binjai) - Ade Dea Putri Pratiwi; Hendra Harmain; Nuri Aslami (Universitas Labuhanbatu, 2023)
PT Permodalan Nasional Madani (Persero) with its PNM Mekaar service has several advantages that make it more attractive than other Bank products in the view of the people of Binjai city, such as the implementation of a rent-sharing system, free collateral as well as other factors in the form of product knowledge and promotions that are considered influential on people's purchasing decisions. This research was conducted with a type of descriptive quantitative research, the population in this study is the people of Binjai city, especially underprivileged women who take financing with a rent-sharing system at PT PNM, samples were taken by accidental sampling technique, selected samples as many as 100 respondents. Primary data collection using questionnaires. The analytical techniques used in this study are Validity Test and Reliability Test, Classical Assumption Test, Multiple Linear Test and Hypothesis Test. PT Permodalan Nasional Madani (Persero) with its PNM Mekaar service has several advantages that make it more attractive than other Bank products in the view of the people of Binjai city, such as the implementation of a rent-sharing system, free collateral as well as other factors in the form of product knowledge and promotions that are considered influential on people's purchasing decisions. This research was conducted with a type of descriptive quantitative research, the population in this study is the people of Binjai city, especially underprivileged women who take financing with a rent-sharing system at PT PNM, samples were taken by accidental sampling technique, selected samples as many as 100 respondents. Primary data collection using questionnaires. The analytical techniques used in this study are Validity Test and Reliability Test, Classical Assumption Test, Multiple Linear Test and Hypothesis Test.Based on the results of the analysis obtained shows that the variables of product knowledge (X1), promotion (X2), rent responsibility system (X3) together have an effect with a significance value shown of 0.000 < 0.05 it is known that the Fcalculate value is smaller than the table of 36.077 > 2.698. The value meets the requirements so that there is a simultaneous significant influence on decision making (Y).PT PNM Binjai unit should continue to maintain the factors that become the community's benchmark in taking financing, especially the factor of implementing a rent responsibility system that is considered good if it is in conducive conditions.